In Silico and In Vitro Studies Unveil the Protective Potential of Diosmin-Hesperidin Conjugate in Doxorubicin Toxicity - A. Adeneye, Adejuwon; M. Abdulrafiu, Taiwo (Al-Nahrain Journal of Science, 2025)
Doxorubicin (DOX), a potent anthracycline antibiotic widely used in cancer therapy, is notorious for inducing off-target multi-organ toxicities. These toxicities arise through mechanisms such as DNA intercalation, topoisomerase II poisoning, oxidative stress via free radical generation, and membrane disruption caused by altered sphingolipid metabolism. Mitigating these adverse effects is essential to improving the therapeutic index of DOX. This study investigates the protective potential of a diosmin-hesperidin conjugate using in silico and in vitro methods. The diosmin-hesperidin conjugate, derived from natural flavonoids, was assessed for its anti-apoptosis and antioxidant potential to alleviate DOX-induced toxicities. In silico analyses, including molecular docking and dynamic simulations, revealed high binding affinities of the conjugate to key oxidative stress-related targets, such as catalase, glutathione reductase, and apoptosis-related proteins (e.g., caspase-3, Hsp70, and Hsp90β). In vitro assays, including DPPH, NO scavenging, FRAP, H₂O₂ scavenging, lipid peroxidation inhibition, and total antioxidant capacity, validated the conjugate’s robust antioxidant activity. The computational and in vitro studies showed that the conjugate stabilized antioxidant enzymes and inhibited apoptotic pathways. Overall, by leveraging the synergistic effects of this flavonoid conjugate, this study highlighted the diosmin-hesperidin conjugate as a promising natural adjunct therapy to mitigate DOX’s off-target oxidative stress- and apoptosis-mediated toxicities. Thus, providing a foundation for further preclinical and clinical evaluations, and contributing to the advancement of natural product-based cancer therapy.